Synthesis and biological evaluation of novel steroidal 5α, 8α-epidioxyandrost-6-ene-3β-ol-17-(O-phenylacetamide)oxime derivatives as potential anticancer agents. Issue 16 (15th August 2017) - Bu, Ming; Cao, Tingting; Li, Hongxia; Guo, Mingzhou; Yang, Burton B.; Zeng, Chengchu; Zhou, Yue; Zhang, Na; Hu, Liming
Graphical abstract: Abstract: Inspired by the significant anti-cancer activity of our previously screened natural ergosterol peroxide (EP, 1 ), we synthesized and characterized a series of novel 5α, 8α-epidioxyandrost-3β-ol-17-( O -phenylacetamide)oxime derivatives (9a –o ). The anti-proliferative activity of the synthesized compounds against human hepatocellular carcinoma cells (HepG2, Sk-Hep1) and human breast cancer cells (MCF-7, MDA-MB231) were investigated. Compounds9d, 9f, 9h, 9j and9m displayed good anti-proliferative activity (most IC50  < 20 μM) in vitro . Furthermore, fluorescence imaging showed that the designed coumarin-9d conjugate (12 ) localized mainly in mitochondria, leading to enhanced anticancer activities over the parent structure.